Inclusive Governance and National Rural Health Mission: A Case study of Pulwama (J&K) - Mir, Tavseef Ahmad; Singh, Manvendra (International Journal of Social Sciences and Management, 2022)
Background: Inclusive governance signifies both processes and outcomes in developmental strategies across the world. More inclusive states are more prosperous, influential, and vibrant. Process-based inclusion refers to the decision and policy-making processes and how, why, and whose voices are considered. Outcome-based inclusion refers to the disbursement of developmental outcomes. One of the government’s programs that it has launched is the National Rural Health Mission (NRHM). This programme is functional all over the Union Territory of Jammu and Kashmir. District Pulwama is part of this region. Objectives: whether this programme meets the area-specific needs and whether there is a need for any modification in the healthcare administration to make the programme more inclusive and efficient. Methods: Sampling, literature review, interviews, questionaries, and focused group discussions are employed. The sample size of participants is one hundred, including doctors, patients, common citizens, paramedical staff and administrators. Results: Results were drawn which showed that the strategic convergence of healthcare and other related programs from village level upwards, context-specific alterations, and workable resources allocation elevate this program’s dynamicity. 80% of respondents favoured area-specific modifications needed to reach all society sections. Conclusion: To meet Sustainable Development Goals within the prescribed time limits, the program can result in a remarkable change in the overall healthcare system. It needs to be in sync with the current healthcare scenario, like the outbreak of pandemics like COVID-19. Suggestions are provided to make it more effective, result-oriented, and in sync with the existing ground realities. Int. J. Soc. Sc. Manage. Vol. 9, Issue-2: 88-93.